Integrated agricultural production systems and the effects of the animal component (Research, Society and Development, 2021)
A large part of the cattle herd in Brazil is found in pasture systems in intertropical areas, such as the Amazon. Given the need to seek greater environmental and economic sustainability of livestock, this work aimed to discuss the introduction and benefits of the animal component in integrated systems of agricultural production. The review was based on the references of bibliographic research collected through the survey of scientific production on integrated systems of agricultural production (SIPA), produced between the years 2000 to 2020. SIPAs consist of the implementation of different activities (livestock, agriculture and forestry) in the same area, in consortium, sequential or rotated, managed with an emphasis on the context of production and sustainability. The inclusion of the animal component brings several benefits to the system, whether by stimulating biomass production, increasing nutrient cycling, increasing microbial mass and diversity, improving physical, active and soil fertility conditions. In addition to being a beneficiary of the system, the animal component benefits from inclusion, especially due to the better nutritional values ​​of forages and the comfort offered by some arrangements. Another beneficial factor of integrated systems for livestock would be their use in alternative methods in the recovery and renewal of pastures in degraded areas. There are several modalities/arrangements that can be used in the integration, in which basics are set up as existing synergies between activities, which have their particular or mutual benefits when properly conducted.